Upper altitudinal and southern geographic range extensions for Cruziohyla craspedopus (Anura: Hylidae) (Funkhouser, 1957) in Ecuador - Núñez, Darwin; Núñez, Darwin; J. Brito; J. Brito (Check List, 2015)
We report the southernmost record of Cruziohyla craspedopus in Ecuador. An adult female was collected in the province of Zamora Chinchipe in southern Ecuador in the Cordillera del Condor. This record increases the previously reported altitudinal range for the species by 468 m and extends the distribution by 105 km to the south.
Centro Jambatu - ID 1559